Bio-molecular gradient surfaces for biological recognition - Fornari, Enzo (2014)
The use of protein microfluidic systems is of growing interest for a variety of applications, including but not limited to tissue engineering, drug delivery and biosensors. The means by which to control chemistries on substrates for biological and medical applications is therefore in high demand. Here the creation of a bio-functional gradient on silica and polymeric surfaces using a micro fluidic technique, for the guidance of cell adhesion and functionality, using AFM tools for protein imaging and force spectroscopy investigation is reported. Atomic force microscopy (AFM) is a high resolution microscopic technique highly used in biological investigations, allowing conformational elucidation of protein deposition on the substrate. In this work application of the techniques of AFM, fluorescence microscopy and cell adhesion studies were used to assess the protein deposition along the microfluidic system. From the fluorescence analysis, it was immediately observed that successful protein immobilization on both substrates was achieved. Differences in fluorescence intensity were also registered along the microfluidic channel (start and end point) suggesting a variation in protein adsorption along the channel. The AFM imaging analysis conducted on the same samples revealed a difference in surface coverage considering the injection and end point (from 70% to 14% respectively) of the protein pattern. The difference in protein density registered along the fibronectin pattern was tested using a functionalised probe AFM technique, allowing molecular resolution of ligands in a physiological environment. A difference in the percentage of observed adhesion events was registered considering the start and end point of the microfluidic pattern, from 90% to 37% respectively. This is likely due to the fact that at the higher surface concentration there is a higher probability of the functionalised tip interacting with multiple fibronectin molecules, as confirmed from the presence of multiple adhesions at start point with a higher adhesion force of 82 pN ± 7.4 pN. To complement the AFM force measurements, protein functionality was tested by investigating the cell adhesion, shape and migration on the protein pattern. The fibronectin protein gradient was shown to control cell adhesion and migration along the patterns, demonstrating that this system can be used for biological applications to monitor the cell behaviour using difference protein concentration and cell density all in the same microfluidic channel. The ability to control cell adhesion and migration on substrates could be of significant interest when researching possible applications in future tissue engineering and biological studies. The combination of AFM and fluorescence microscopy techniques for protein density investigation used in this work demonstrated that protein deposition and arrangement on substrate play an important role in cell adhesion and migration studies.